Debt restructuring in the euro area: How can sovereign debt be restructured more effectively? - Christoph Große Steffen; Julian Schumacher (DIW Economic Bulletin, 2014)
The International Monetary Fund (IMF) stated in spring of this year that a more timely restructuring of Greece's sovereign debt would have been beneficial. But what are the available options for early debt restructuring? The report argues that current reforms in the Euro area, in particular, introducing collective action clauses, are unlikely to be sufficient in their present form. Alternatively, a statutory solution in the form of an international or European insolvency regime for sovereign states is difficult to implement politically. Therefore, the contractual approach to debt restructuring should be facilitated by redesigning future contracts for bonds in the euro area. Specifically, more powerful collective action clauses should be included in bond contracts and the ratable payment provision of all creditors should be reformed in order to limit the impact of legal disputes in the event of a debt restructuring. This approach would simplify future debt restructuring operations and make the no-bailout rule more credible, thus re-activating the disciplinary effect of interest rates on governments.
Keywords: D78; F34; K12; K33; 330; Sovereign debt; International financial assistance; Holdout; Coordination problem; Collective action clauses